Isolated Bilateral Cerebellar Dysfunction as the Initial Manifestation of HIV Infection: A Diagnostic Challenge, Case Report, and Literature Review - Ritwick Mondal; Shramana Deb; Ananya Sengupta; Subhadeep Banerjee; Nirmalya Ray; Mona Tiwari; Jayanta Roy; Julián Benito-León (The Cerebellum, 2025)
Despite widespread access to antiretroviral therapy, neurological complications remain common in people living with human immunodeficiency virus (HIV). While opportunistic infections and HIV-associated malignancies are the usual causes, there is growing recognition of atypical, non-opportunistic neurological syndromes as early manifestations of HIV infection—even in the absence of prior diagnosis or treatment. We report the case of a 46-year-old woman with type 2 diabetes mellitus and a history of pulmonary tuberculosis who presented with a two-month history of progressive unsteady gait, dysarthria, and frequent falls. Neurological examination revealed isolated cerebellar dysfunction. Brain magnetic resonance imaging showed T2 and FLAIR hyperintensities in the bilateral middle cerebellar peduncles and adjacent white matter, suggestive of rhombencephalitis. Extensive diagnostic work-up for infectious, autoimmune, and paraneoplastic etiologies was negative. HIV testing revealed dual seropositivity for HIV-1 and HIV-2, with undetectable HIV-1 RNA and a low CD4 + T-cell count. The patient improved clinically with supportive care and was referred for antiretroviral therapy. At the two-month follow-up, she demonstrated marked recovery. Although cerebellar involvement in HIV is typically associated with opportunistic infections or neoplasia, this case illustrates that bilateral cerebellar dysfunction can represent the first clinical manifestation of HIV infection. We also review previously reported cases in which cerebellar signs were the initial presentation, emphasizing the need to consider HIV testing in patients with unexplained cerebellar syndromes.

Norovirus-associated neurological manifestations: summarizing the evidence - Shramana Deb; Ritwick Mondal; Durjoy Lahiri; Gourav Shome; Aakash Guha Roy; Vramanti Sarkar; Shramana Sarkar; Julián Benito-León (Journal of NeuroVirology, 2023)
Norovirus, a positive-stranded RNA virus, is one of the leading causes of acute gastroenteritis among all age groups worldwide. The neurological manifestations of norovirus are underrecognized, but several wide-spectrum neurological manifestations have been reported among infected individuals in the last few years. Our objective was to summarize the features of norovirus-associated neurological disorders based on the available literature. We used the existing PRISMA consensus statement. Data were collected from PubMed, EMBASE, Web of Science, and Scopus databases up to Jan 30, 2023, using pre‐specified searching strategies. Twenty-one articles were selected for the qualitative synthesis. Among these, seven hundred and seventy-four patients with norovirus-associated neurological manifestations were reported. Most cases were seizure episodes, infection-induced encephalopathy, and immune-driven disorders. However, only a few studies have addressed the pathogenesis of norovirus-related neurological complications. The pathogenesis of these manifestations may be mediated by either neurotropism or aberrant immune-mediated injury, or both, depending on the affected system. Our review could help clinicians to recognize these neurological manifestations better and earlier while deepening the understanding of the pathogenesis of this viral infection.

Meningoencephalitis associated with COVID-19: a systematic review - Ritwick Mondal; Upasana Ganguly; Shramana Deb; Gourav Shome; Subhasish Pramanik; Deebya Bandyopadhyay; Durjoy Lahiri (Journal of NeuroVirology, 2021)